Objectifying Specific and Nonspecific Effects of Acupuncture: A Double-Blinded Randomised Trial in Osteoarthritis of the Knee. (10th January 2013) - Karner, Max; Brazkiewicz, Frank; Remppis, Andrew; Fischer, Joachim; Gerlach, Oliver; Stremmel, Wolfgang; Subramanian, Shanmuga Velayutham; Greten, Henry Johannes
Abstract : Introduction . Acupuncture was recently shown to be effective in the treatment of knee osteoarthritis. However, controversy persists whether the observed effects are specific to acupuncture or merely nonspecific consequences of needling. Therefore, the objective of this study is to determine the efficacy of different acupuncture treatment modalities. Materials and Methods . We compared between three different forms of acupuncture in a prospective randomised trial with a novel double-blinded study design. One-hundred and sixteen patients aged from 35 to 82 with osteoarthritis of the knee were enrolled in three study centres. Interventions were individualised classical/ modern semistandardised acupuncture and non-specific needling. Blinded outcome assessment comprised knee flexibility and changes in pain according to the WOMAC score. Results and Discussion . Improvement in knee flexibility was significantly higher after classical Chinese acupuncture (10.3 degrees; 95% CI 8.9 to 11.7) as compared to modern acupuncture (4.7 degrees; 3.6 to 5.8). All methods achieved pain relief, with a patient response rate of 48 percent for non-specific needling, 64 percent for modern acupuncture, and 73 percent for classical acupuncture. Conclusion . This trial establishes a novel study design enabling double blinding in acupuncture studies. The data suggest a specific effect of acupuncture in knee mobility and both non-specific and specific effects of needling in pain relief.